Optimalisasi Daya Nalar Kritis Siswa dalam Pelajaran PAK dengan Model Pembelajaran PBL dengan Bantuan Mind Mapping Fase F Kelas 11 SMKN 1 Sintang - Christianus Pudali (PROSIDING SEMINAR NASIONAL PENDIDIKAN DAN AGAMA, 2025)
This study aims to optimize students' critical reasoning power in Catholic Religious Education (PAK) subjects by applying the Problem-Based Learning (PBL) learning model combined with mind mapping techniques. The research was conducted in class 11 of SMKN 1 Sintang with a Classroom Action Research (CAR) approach consisting of two cycles. Data were collected through observations, interviews, learning outcome tests, and teacher reflections. The results showed that the application of PBL model with the help of mind mapping improved students' critical reasoning power. This improvement can be seen from the increase in students' ability to identify problems, analyze information, and formulate logical and structured arguments. Thus, this learning strategy can be an effective solution in improving students' critical thinking skills.